Evaluation of Specific Antibody against Recombinant CFP-10 Protein of Mycobacterium Tuberculosis in Patients with Tuberculosis - Mina Karami; Majid Tebianian (مجله دانشکده پزشکی اصفهان, 2015)
Background: Tuberculosis (TB) has been remained as a major health problem. The most commonly used diagnostic tool for TB is a simple skin test. However, it has some disadvantages and it`s specificity can be compromised. Hence, detection of Mycobacterium tuberculosis specific antibodies in human sera has been considered as an important diagnostic test. Methods: In this study, humoral immune responses against recombinant CFP-10 protein of Mycobacterium tuberculosis in 51 patients with TB and 39 healthy subjects were evaluated using indirect enzyme-linked immunosorbent assay (ELISA). Findings: From 51 positive serum samples, 47 were positive and from 39 negative serum samples, 33 showed negative results. In this study, sensitivity and specificity of test were 92.15, 84.61 percent for dilution of 1:10 and 64.70 and 97.43 percent for dilution of 1:100, respectively. Accordingly, the estimated cut-off point was 0.351 and .025 for dilutions of 1:10 and 1:100, respectively. Conclusion: Our data suggested that the levels of antibodies against CFP-10 antigens in patients with TB were significantly higher than those in healthy subjects. This study demonstrated that ELISA with the use of the CFP-10 recombinant antigens is simple and sensitive and can be used to analyze large numbers of samples for the serodiagnosis of TB.